Consultant–client relationship and knowledge transfer in small- and medium-sized enterprises change processes - Martinez, L. F.; Ferreira, A. I.; Can, A. B. (Psychological Reports, 2016)
Based on Szulanski’s knowledge transfer model, this study examined how the communicational, motivational, and sharing of understanding variables influenced knowledge transfer and change processes in small- and medium-sized enterprises, particularly under projects developed by funded programs. The sample comprised 144 entrepreneurs, mostly male (65.3%) and mostly ages 35 to 45 years (40.3%), who filled an online questionnaire measuring the variables of “sharing of understanding,” “motivation,” “communication encoding competencies,” “source credibility,” “knowledge transfer,” and “organizational change.” Data were collected between 2011 and 2012 and measured the relationship between clients and consultants working in a Portuguese small- and medium-sized enterprise-oriented action learning program. To test the hypotheses, structural equation modeling was conducted to identify the antecedents of sharing of understanding, motivational, and communicational variables, which were positively correlated with the knowledge transfer between consultants and clients. This transfer was also positively correlated with organizational change. Overall, the study provides important considerations for practitioners and academicians and establishes new avenues for future studies concerning the issues of consultant–client relationship and the efficacy of Government-funded programs designed to improve performance of small- and medium-sized enterprises.